The role of Muslim devotional practices in the reversal of language shift. Issue 1 (2nd January 2017) - Rosowsky, Andrey
ABSTRACT: Fishman's scale for evaluating language vitality proposes a stage in language shift where exclusively the older generation takes part in 'rituals', 'concerts' and 'songfests' in the minority language. Once this generation dies away, according to the scale, these cultural practices disappear with them. Within certain Muslim youth communities in the UK, counter examples exist where the younger generation leads the way in reviving, performing and extending the repertoire of this religio-cultural heritage. Although this emerging expanded repertoire of song and poetry is clearly multilingual in nature, recitation and performance of the community heritage languages, Urdu and Punjabi, feature strongly. What remains to discover is whether such increasing familiarity with poetic language and form can impact positively on reversing the language shift these communities are experiencing in their third and fourth generations. Although there is evidence that singing and reciting in other minority language settings, secular and religious, are not infrequent pursuits of youth, it is argued in this article that an accompanying religious revival provides an important extra, galvanising, boost to the process of possible reversing language shift. It is suggested that available scales for evaluating language vitality are inadequate in the face of complex diasporic minority language settings.